Key Elements of a Family Intervention for Schizophrenia: A Qualitative Analysis of an RCT - Grácio, Jaime; Gonçalves‐Pereira, Manuel; Leff, Julian (Family process, 2018)
Schizophrenia is a complex biopsychosocial condition in which expressed emotion in family members is a robust predictor of relapse. Not surprisingly, family interventions are remarkably effective and thus recommended in current treatment guidelines. Their key elements seem to be common therapeutic factors, followed by education and coping skills training. However, few studies have explored these key elements and the process of the intervention itself. We conducted a qualitative and quantitative analysis of the records from a pioneering family intervention trial addressing expressed emotion, published by Leff and colleagues four decades ago. Records were analyzed into categories and data explored using descriptive statistics. This was complemented by a narrative evaluation using an inductive approach based on emotional markers and markers of change. The most used strategies in the intervention were addressing needs, followed by coping skills enhancement, advice, and emotional support. Dealing with overinvolvement and reframing were the next most frequent. Single‐family home sessions seemed to augment the therapeutic work conducted in family groups. Overall the intervention seemed to promote cognitive and emotional change in the participants, and therapists were sensitive to the emotional trajectory of each subject. On the basis of our findings, we developed a longitudinal framework for better understanding the process of this treatment approach. La esquizofrenia es una enfermedad biosicosocial compleja en la cual la emoción expresada en los familiares es un predictor firme de recaídas. Como era de esperar, las intervenciones familiares son notablemente eficaces y, en consecuencia, recomendadas en las pautas de los tratamiento actuales. Sus elementos fundamentales parecen ser los factores terapéuticos comunes, seguidos de la capacitación en educación y en habilidades de afrontamiento. Sin embargo, pocos estudios han analizado estos elementos clave y el proceso de intervención en sí. Realizamos un análisis cualitativo y cuantitativo de los registros de un ensayo de una intervención familiar de vanguardia que aborda la emoción expresada, y que fueron publicados por Leff y colegas hace cuatro décadas. Los registros se analizaron en categorías y se examinaron los datos utilizando estadísticas descriptivas. Esto se complementó con una evaluación narrativa utilizando un enfoque inductivo basado en marcadores emocionales y marcadores de cambio. Las estrategias más utilizadas en la intervención fueron el abordaje de necesidades, la mejora de las habilidades de afrontamiento, el consejo y el apoyo emocional. Las siguientes estrategias más frecuentes fueron el manejo de la sobreprotección y el replanteamiento. Las sesiones domiciliarias con una sola familia parecieron potenciar el trabajo terapéutico realizado en grupos familiares. En general, la intervención pareció promover el cambio cognitivo y emocional en los participantes, y los terapeutas tuvieron en cuenta la trayectoria emocional de cada sujeto. Basándonos en los resultados, desarrollamos un marco longitudinal para comprender mejor el proceso del enfoque de este tratamiento. 精神分裂症是一个复杂生物心理社会症状,而家庭成员表现出的情感是其有力的复发预测因子。毫不奇怪,家庭干预措施对此非常有效,并因此在当前治疗准则中得到推荐。它们的关键因素似乎是普遍治疗因素,结合教育和应对技能训练。然而,很少有研究探讨这些关键因素及其干预过程。我们对一项针对表达情感的,由Leff 及其同事在40年前发表的开拓性家庭干预实验记录进行了定性和定量分析。我们对记录进行分类分析,并使用描述统计学对数据进行探讨。应用一项基于情感标记和变化标记的感应方法,该方法通过一项叙事评估方法得到补充。干预措施中最常使用的策略是应对需求,以及应对技能增强,建议,以及情感支持。其次是处理过度参与和重塑。单个家庭疗程似乎会增强家庭组群中的治疗工作。总体而言,干预措施似乎会促进参与者认知和情感变化,而心理治疗师对每个个体情感轨迹有敏锐观察。基于我们的发现,我们发展了一个更好理解该治疗方法过程的纵向框架。